Multimodal-Pragmatic Analysis of Arabic–Indonesian Subtitle Translation in the Animated Film Muhsin and Mahasin: The Episode “The Danger of Boasting” - Yulia Yuliani, Sri; Zaka Al Farisi, Mohamad; Supriadi, Rinaldi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2025)
The study of subtitle translation in religious animated films has become increasingly significant as it requires not only linguistic equivalence but also the ability to construct pragmatic meaning through the integration of multiple communicative modes. The episode “Bahaya Pamer” from the animation Muhsin and Mahasin serves as an interesting object of analysis because it conveys Islamic moral values of modesty through verbal and visual interactions rich in educational messages. This research analyzes the Arabic–Indonesian subtitle translation strategies and the role of multimodality in constructing pragmatic meaning and supporting the delivery of moral messages. Employing a qualitative approach with content analysis, the study examines eight dialogue segments containing speech acts and multimodal elements encompassing visual, auditory, and gestural dimensions. Drawing upon Speech Act Theory (Searle, 1979), Multimodal Discourse Analysis (Kress & van Leeuwen, 2006), and the audiovisual translation strategies model (Díaz Cintas & Remael, 2021), the findings reveal that literal transfer, adaptation, and expansion are dominant strategies used to adjust emotional and cultural contexts of the target audience. The coherence among modes reinforces pragmatic meaning and highlights the relationship between language, moral values, and visual context.